"Psychological Swollen Cheek" and Tragedy of Estrangement in Sherwood Anderson's Works - S M Pinaev (Peoples' Friendship University of Russia (RUDN University), 2013)
The article deals with the psychological conflicts in Sherwood Anderson's prose. The author reveals the nature of estrangement in the short stories from the book "Winesburg, Ohio" (1919).